Self‐Assembly of [2+2] Platina Macrocycles Using a Flexible Organometallic Clip. Issue 14 (18th May 2017) - Jana, Achintya; Das, Neeladri
Abstract: Synthesis of a new pyrazine‐based "flexible" and ditopic platinum(II) organometallic clip (3 ) is being reported. Flexibility is incorporated by ether functional groups that bridge the rigid core (pyrazine) and periphery (Pt II centers). Its self‐assembly with various dicarboxylates in a 1:1 stoichiometric ratio yields [2 + 2] dimeric neutral metallacycles (4 –6 ). Formation of macrocycles was supported by multinuclear NMR, ESI‐MS and elemental analyses. Crystal structure of one of the macrocycles confirmed its rectangular shape. The geometry of each supramolecular structure was optimized by using PM6 semiempirical molecular orbital method. Abstract : A new pyrazine‐based ditopic Pt(II) organometallic clip has been designed that is "flexible" due to presence of ether functional groups bridging the core (pyrazine) and periphery (Pt II units). It self‐assembles with dicarboxylates to yield nanoscalar metallacycles.